Assessing Outpatients' Knowledge, Attitude, and Practice Toward Managing Diabetes in Saudi Arabia. (17th March 2022) - Mansy, Wael; Wajid, Syed; Alwhaibi, Abdulrahman; Alghadeer, Sultan M.; Alhossan, Abdulaziz; Babelghaith, Salmeen; Alrabiah, Ziyad; Al Arifi, Mohamed N.
Introduction: When it comes to non-communicable diseases like diabetes, inadequate knowledge, attitude, and practice are often linked to poor health outcomes. This study aims to assess the patients' knowledge, attitude, and practice (KAP) of diabetes in the outpatient department of a university teaching hospital in Saudi Arabia. Methodology: In this cross-sectional study, diabetes type 2 patients attending outpatient departments at a university teaching hospital, Riyadh, were assessed regarding their knowledge, attitude, and practice toward diabetes using a validated KAP scale. Descriptive and inferential analysis was done to determine the factors associated with KAP score using SPSS version 26.0 software (SPSS Inc., Chicago, IL, U.S.). Results: Males made up 69.7% of the sample (n = 165), while 56.9% were between the ages of 41 and 75. The level of knowledge and practice had "good" in 37.6%, and 47.9%, respectively, but level of attitude had "positive" in 30.9% of patients. The association between knowledge tier and gender (p0.014) and insurance status (p0.008), respectively, was shown to be significant. However, the attitude tier was only significantly associated with gender ( P = .003). The practice tier also showed a significant age association ( P = .049). As regards, the mean scores for diabetes-related knowledge were higher only among insured participants ( P = .03) than for other participants' sociodemographic factors. Meanwhile, the mean attitude scores were also higher among males ( P = .006) than for other sociodemographic characteristics. A comparison of the participants' sociodemographic characteristics found no statistically significant variations in practice scores. Conclusion: Unfortunately, this study found that outpatient diabetes patients had insufficient knowledge, practice, and a negative attitude toward diabetes type 2. This imposes a great burden on healthcare workers and hence the healthcare system to improve patient scores via diabetes education programs or pharmacist-led patient counseling initiatives.